Cholinergic alterations by exposure to pesticides used in control vector: Guppies fish (Poecilia reticulta) as biological model - Toledo-Ibarra, G. A.; Rodríguez-Sánchez, E. J.; Ventura-Ramón, H. G.; Díaz-Resendiz, K. J. G.; Girón-Pérez, M. I. (International journal of environmental health research, 2018)
Spinosad and temephos are two of the most used pesticides in Mexico for the control of vector causing disease such as dengue, chikungunya and Zika. The aim of this study was to compare the neurotoxic effects of these two pesticides using guppy fish (Poecilia reticulata) as a model organism. Guppies were exposed for 7 and 21 days to technical grade temephos and spinosad at 1.0 and 0.07 g/L, respectively, (10 and 0.5 mg/L of active substance; concentrations recommended by the Ministery of Health of the State (Secretaría de Salud de Nayarit (SSN) Mexico)). Subsequently, acetylcholinesterase activity (AChE) and acetylcholine concentrations (ACh) in muscle tissue were determined. Temephos exposure decreased AChE activity and increased ACh concentration, whereas exposure to spinosad only increased ACh concentration. Though cholinergic alterations were more severe in fish exposed to temephos, both pesticides were equally lethal during the first seven days after exposure. Nonetheless, temephos was more lethal after 21 days.